failures in composite restoration - Mahajan, Vishal; Bhondwe, Sarvesha; Doot, Rohit; Balpande, Rupali; Bhandari, Sonam; Dahiwale, Sonali (International Journal of Dental Research, 2015)
In recent years, the popularity of tooth colored restorative material has led to a rapid increase in the use of resins. This critical review paper is meant to be useful contribution to the recognition & understanding of problems related to the failures of composite restoration. This review categorizes the challenges as those related to the restorative materials, the dentist and the patients. In spite of the major improvements in both physical and mechanical characteristics following factors are still of major concern, such as improper case selection, isolation, wear resistance, cavity preparation, placement of composites, curing, finishing & polishing. Major problems associated with composites failures are polymerization shrinkage & contraction stress related to polymerization shrinkage, water sorption, solubility, discoloration of restoration (staining), elution of material from restoration, marginal failures, secondary caries, and fracture of the restoration, post-operative sensitivity, and micro-leakage.